Recent advances in hierarchical anode designs of TiO2-B nanostructures for lithium-ion batteries - Tuyet Nhung Pham (Wiley Online Library, 2021)
The state-of-the-art development progress of the fabrication, design, modification, and applications of TiO2-B-based hierarchical nanostructures with a well-controlled size and morphology in lithium-ion battery (LIB) applications has been summarized and discussed. Based on studying on lithiation/delithiation on mechanisms of a typical metal oxide nanomaterials, along with doping with foreign atoms (metal or non-metal), using electronically conductive additives (graphene/graphene derivatives), as well as designing and using hierarchical anode-material nanostructures (hybrids/composites) containing two or more constituents in LIB applications, these strategies have provided many great opportunities to take maximum advantage of both the high capacity and rate capacity while avoiding significant capacity loss after charge/discharge cycling. In this review, the advances in TiO2-B-based anode structures at the nanoscale for LIBs have been discussed in two major sections, including (a) hierarchical heterostructures based on TiO2-B and metal, non-metal, transition metal oxides (TMOs), and transition metal dichalcogenides (TMDs); and (b) hybrid designs/nanocomposites between TiO2-B and graphene/graphene derivatives. The in-depth understanding of structure-property relationships as well as detailed suggestions on the mechanism, reason, and origin of the excellent enhancement in electrochemical performance in the above strategies, has been presented and highlighted.